Compudose® implant vs a Ralgro® plus Synovex-S® reimplant program for finishing steers - S. Laudert; J. Eder; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1983)
Compudose implanted feedlot steers performed similarly to steers initially implanted with Ralgro and reimplanted with Synovex-S. Steers lost 2.9% of the Compudose implants.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Implant; Reimplant; Finishing steers